Sensory Violence within Spanish Baroque Drama: Women Murdered on Stage - Ponce, Clara Bonet (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2025)
This article takes a multi-sensory approach to the baroque drama de honra in order to enlighten the sensory expectations (thirst for blood and body horror) of the public who came to witness how several women accused of adultery were killed on stage. In this case, the effects of the tragedy are constructed from uxoricides sometimes performed in explicit sacrificial rituals. Thus, every studied play contributes to the creation of a school of exemplarity in the emotional community of theatregoers through the morbid excitement of the senses aroused by violence. From Doña Mencía’s ritualistic death in El médico de su honra (1635) to the Machiavellian manslaughter orchestrated by the Duke of Ferrara in El castigo sin venganza (1631), smell, touch, sight, and hearing all play a role in the configuration of the oppressive atmospheres that are characteristic of honour plays. Acting stimulates the senses of the audience, who thereby perceives the endangered corporeality of the murdered women. Their deaths, represented in an exceptional way, are key to the reception of the four comedias analyzed here.